Inventarisasi dan Identifikasi Hama Utama Kedelai Pada Fase Pertumbuhan Generatif Tanaman Kedelai (Glycine Max (L.) Merril) Di Kebun Percobaan Manggoapi Fakultas Pertanian Universitas Papua - Juarti Rahayu; Yacob Bodang; Sutiharni; Adelin Elsina Tanati; Antonius Suparno (Agrotek, 2020)
This study aimed to inventory and identify the types of insect pests that damage soybean plants in the generative phase and describe the symptoms of damage caused. The results showed that there were 6 (six) main insect pests that caused damage to soybean plants in the generative phase, namely Phaedonia inclusa, Nezara viridula, Riptortus linearis, Chrysodeixis chalcites, Etiella zinckenella, and Lamprosema indicata. It was suspected that the presence of these 6 types of insects was influenced by two factors, namely internal factors (the characteristics possessed by the insect itself such as the ability to reproduce, the nature or how to maintain themselves and also the age of the insect) and external factors that was climatic factors such as temperature, humidity and rainfall (Jumar, 2000). The 6 pests were found to damage soybean plants by biting and chewing plant parts, but there were also those that damaged plants by piercing and sucking plant fluids.